2022
DOI: 10.1021/acssuschemeng.2c01765
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Approach for Pt Single Atoms Deposition on Two-Dimensional Calcium Niobate Nanosheets for Photocatalytic Hydrogen Evolution

Abstract: Single atoms (SAs) have drawn significant attention, because of their enormous catalytic activity and high atom-utilization efficiency. Particularly, for H 2 evolution, SAs decorated on two-dimensional (2D) nanosheets have great potential, because of the distinctive advantages offered by 2D materials, such as abundant surfaceactive sites, high specific surface area, and better-photoexcited charge carrier separation. Despite the significant advantages of 2D materials as support, the deposition of SAs on 2D nano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…The XRD pattern of flocculated CNO nanosheets is in agreement with previous literature. 26,32 The XRD pattern of the BFO-Co/CNO sample mainly shows diffraction peaks of BFO due to its higher contents, and the attenuated peak of CNO in the composite is attributable to its presence and excellent dispersion. The successful synthesis of BFO was also confirmed via FTIR (Figure 1d) spectra where two fundamental bands at ∼441 and ∼548 cm −1 were observed that are characteristics of Fe−O stretching and bending Nb−OH and Nb�O present on the surface of the nanosheets, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The XRD pattern of flocculated CNO nanosheets is in agreement with previous literature. 26,32 The XRD pattern of the BFO-Co/CNO sample mainly shows diffraction peaks of BFO due to its higher contents, and the attenuated peak of CNO in the composite is attributable to its presence and excellent dispersion. The successful synthesis of BFO was also confirmed via FTIR (Figure 1d) spectra where two fundamental bands at ∼441 and ∼548 cm −1 were observed that are characteristics of Fe−O stretching and bending Nb−OH and Nb�O present on the surface of the nanosheets, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…KCa 2 Nb 3 O 10 layered material was prepared using K 2 CO 3 , CaCO 3 , and Nb 2 O 5 in K/Ca/Nb = 1.05/2/3 molar ratio according to the previous report . The mixture was calcined for 12 h at 1200 °C at a 10 °C/min rate.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Furthermore, by creating bonds as a conductive layer through the unsaturated coordination atoms close to the Ov, they can also quicken the interfacial charge transfer. [24][25][26] As a result, the addition of Ov allows for the quick migration of photogenerated electrons from the semiconductor body to the noble metal in order to reduce oxygen and produce O 2…”
Section: Introductionmentioning
confidence: 99%
“…23 Furthermore, by creating bonds as a conductive layer through the unsaturated coordination atoms close to the Ov, they can also quicken the interfacial charge transfer. 24–26 As a result, the addition of Ov allows for the quick migration of photogenerated electrons from the semiconductor body to the noble metal in order to reduce oxygen and produce ˙O 2 − , while also enriching the photogenerated vacancies at the catalyst's interface in contact with the noble metal. 27 This stimulates the formation of ˙O 2 − to interact more quickly with the intermediates formed during the oxidation of HMF to produce DFF.…”
Section: Introductionmentioning
confidence: 99%